Interactive-excited waterdrop triboelectric nanogenerator with ultrahigh charge density and instantaneous power. (15th June 2022) - Luo, Hongchun; Gu, Guangqin; Shang, Wanyu; Zhang, Wenhe; Cui, Peng; Zhang, Bao; Guo, Junmeng; Zheng, Mingli; Cheng, Gang; Du, Zuliang
Abstract: In recent years, waterdrop triboelectric nanogenerator (WD-TENG) has attracted much attention in the field of energy harvesting. However, the charge density of waterdrop after friction with other materials is low, limiting the output performance and real application of WD-TENGs. For solving this problem, an interactive-excited strategy is introduced here by combining a WD-TENG and a Kelvin waterdrop generator. As excited by WD-TENG, Kelvin waterdrop generator becomes much easier to start electrification with controllable polarity. As excited by Kelvin waterdrop generator in return, the hugely improved output performances of WD-TENG are achieved. The charge quantity of a single waterdrop reaches 144 nC, and the corresponding charge density is as high as 2304 nC/mL. The output voltage and instantaneous power reach as high as 1760 V and 54.6 mW, respectively. The obtained parameters of charge density and instantaneous power are much more than previous records of WD-TENGs. Also, it has been demonstrated that a single waterdrop of 62.50 μL can light up 320 LEDs. The interactive-excited strategy hugely improves the charge density and instantaneous power of WD-TENG, which has promising applications in harvesting waterdrop energy and developing self-powered systems. Graphical Abstract: As excited by WD-TENG, Kelvin waterdrop generator becomes much easier to start electrification with controllable polarity. As excited by Kelvin waterdrop generator in return, the output performances of WD-TENG are hugely improved. The transferred charge and instantaneous power of WD-TENG is 144 nC and 54.6 mW, respectively, much more than that of previous reports. ga1 Highlights: An interactive-excited strategy is introduced here by combining a WD-TENG and a Kelvin waterdrop generator. As excited by WD-TENG, Kelvin waterdrop generator becomes much easier to start electrification with controllable polarity. As excited by Kelvin waterdrop generator in return, the hugely improved output performances of WD-TENG are achieved. The interactive-excited strategy hugely improves the charge density and instantaneous power of WD-TENG.